2019
DOI: 10.15171/ps.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Analysis of the Essential Oils of Selected Endemic Edible Apiaceae Plants Root from Caspian Hyrcanian Region (North of Iran)

Abstract: Background: Different endemic species of Apiaceae that widely grow in Hyrcanian region have long been used as spices and herbal remedies. Chemical compositions and bioactivity of many of these plants have not been studied scientifically. The volatile constituents and antimicrobial activity of four edible Apiaceae plants—Elaeosticta glaucescens Boiss, Malabaila secacul (Mill.) Boiss, Caucalis platycarpos L., and Eryngium caucasicum Trautv—roots were investigated. Methods: Gas chromatography/mass spectrometry (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Regarding the observed antimicrobial activity, in view of the results presented in Figure 3 (in which the effectiveness of the U. tomentosa bark extract and that of its main constituent were very similar), it may tentatively be mainly attributed to octyl isobutyrate. Nonetheless, a contribution of mitraphylline (the second major constituent) cannot be ruled out, given that both phytochemicals have been shown to feature antimicrobial activity in the literature [29][30][31][32][33][34][35][36] (see Table S2). In relation to the activity of COS, it is well established and may be ascribed to several mechanisms of action [37], including increased permeability of plasma membrane and the leakage of cellular contents, deprivation of trace elements essential for fungal normal growth due to its chelating action, and inhibition of mRNA synthesis and affection of protein and enzyme production due to binding to fungal DNA.…”
Section: Comparison Of In Vitro Activitymentioning
confidence: 99%
“…Regarding the observed antimicrobial activity, in view of the results presented in Figure 3 (in which the effectiveness of the U. tomentosa bark extract and that of its main constituent were very similar), it may tentatively be mainly attributed to octyl isobutyrate. Nonetheless, a contribution of mitraphylline (the second major constituent) cannot be ruled out, given that both phytochemicals have been shown to feature antimicrobial activity in the literature [29][30][31][32][33][34][35][36] (see Table S2). In relation to the activity of COS, it is well established and may be ascribed to several mechanisms of action [37], including increased permeability of plasma membrane and the leakage of cellular contents, deprivation of trace elements essential for fungal normal growth due to its chelating action, and inhibition of mRNA synthesis and affection of protein and enzyme production due to binding to fungal DNA.…”
Section: Comparison Of In Vitro Activitymentioning
confidence: 99%
“…The inhibitory effects of this product were higher compared to 14 antibiotics with the exception of meropenem, imipenem, piperacillin, chloramphenicol, cephalothin and cefepime antibiotics (P < 0/05). Most of the compounds in the essential oil of this plant, including terpenes, alcohols and aromatic compounds have been shown to have antibacterial effects in other studies [54,40]. It may be because of the diversity of these antimicrobial molecules in the essential oil that their antimicrobial effects are greater than those of ethanolic and aqueous extracts.…”
Section: Discussionmentioning
confidence: 94%
“…Numerous factors are involved in this difference in e cacy, including plant cultivar, environmental conditions affecting plant growth, extracting components, the type of solvent used for extraction and resistance of isolates [40]. The MIC and MBC, as well as the mean diameter of the growth inhibition zone caused by ethanolic and aqueous extracts of Eryngium caucasicum Trautv were different from other studies, although most of the antimicrobial studies have been based on the essential oil of this plant [40,41] In a report published by Thiem et al [42], the antimicrobial activity of leaves and roots ethanolic extracts of three species of Eryngium, including Eryngium planum, Eryngium campestre and Eryngium maritimum, was evaluated against gram-positive Staphylococcus aureus and Bacillus subtilis. Their ndings showed that the leaves extract effect on S. aureus was greater than B. subtilis while the root extract effect was the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…Rare studies were carried out on this small genus. Hamedi et al studied the essential oil composition of E. glaucescens [ 21 ]. The aliphatic ester constituted 52.0%, followed by the sesquiterpene hydrocarbon (6.1%), which are the major reported classes of the secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%